THE EFFECTIVENESS OF ORAL RETELLING STRATEGY AND WRITTEN RETELLING STRATEGY ON STUDENTS’ READING COMPREHENSION: A COMPARISON - Ekaningrum, Vindy Cahya (English Department of Faculty of Tarbiyah and Teacher Training, 2017)
Reading comprehension skill is important in our social lives which relates to texts, emails, networking sites, and many others. In order to find an effective teaching reading technique, there are studies conducted and developed. One of the strategies to teach reading is called retelling. Many studies found that retelling strategy is effective to teach reading comprehension (Sylvia(2015); Ebaugh (2013); Schisler (2008)). However, there is a contradictory result between those studies found related to the implementation of two types of retelling strategy: oral and written retelling. Sylvia?s (2015) study claims that the written retelling significantly better than oral retelling strategy. However, Schisler?s (2008) study shows result in vice versa. Ebaugh?s (2013) study reveals that there were no significant differences between those two strategies. From the contradictory results seen from previous studies, further study is still needed to figure out more reliable research result on the effectiveness of both strategies.